A dimmable LED system with wireless power and color control - Ong, Han Wei (Nanyang Technological University, 2023)
This is a practical project that involves the design and implementation of LED drivers for warm-white and cool-white lighting-emitting-diode (LED) system. The student is also expected to develop a wireless control for the dimming and color control.